'Don't let the side down, old boy': interrogating the traitor in the 'radical' television dramas of John le Carré and Dennis Potter. Issue 3 (2nd July 2020) - Oldham, Joseph
ABSTRACT: This article examines three British television plays which draw upon political and aesthetic radicalism to examine the Cold War traitor. John le Carré's The End of the Line (1970) uses a traitor's interrogation to create an absurdist vison of Cold War espionage whilst Dennis Potter's Traitor (1971) uses experimental flashback techniques to explore the motives and moral ambiguities surrounding treachery. Although le Carré's later novel Tinker Tailor Soldier Spy (1974) closes off radical possibilities offered by these plays, Potter's Blade on the Feather can be read as a riposte, redeploying the former's generic and heritage conventions to newly subversive ends.